Forgotten continent the battle for Latin America's soul - Reid, Michael (Yale Univ. Press, 2007)
Latin America has often been condemned to failure. Not as poor as Africa, nor as booming as India and China, it has largely been overlooked. Yet this vast continent, home to half a billion people, the world's largest reserves of arable land, and 8.5 percent of global oil, is transforming its political and economic landscape. This book argues that Latin America's efforts to build fairer and more prosperous societies make it one of the world's most vigorous laboratories for capitalist democracy. In many countries--including Brazil, Chile and Mexico--democratic leaders are laying the foundations for faster economic growth and more inclusive politics, as well as tackling deep-rooted problems. Failure will increase the flow of drugs and illegal immigrants to the United States and Europe, jeopardize stability in a region rich in strategic commodities, and threaten some of the world's most majestic natural environments.--From publisher description.
Includes bibliographical references and index
Keywords: Geschichte; Politik; Wirtschaft; Democracy -- Latin America -- History; Populismus; Wirtschaftsentwicklung; Demokratie; Lateinamerika; Latin America -- Politics and government -- 1980-; Latin America -- Economic conditions -- 1982-